1996
DOI: 10.1155/1996/75210
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic and Radiographic Studies of Intrahepatic Metastasis Hepatocellular Carcinoma; The Role of Efferent Vessels

Abstract: The efferent vessel of hepatocellular carcinoma (HCC) and the mechanism and pathogenesis of the high frequency of intrahepatic metastasis in HCC has not yet been clarified. Three hundred ninety-three resected specimens of HCC were examined for tumor thrombosis in the portal vein and the hepatic vein: 231 tumors <-5 cm in diameter were examined for the relationship between mode of tumor spread and tumor size. Efferent vessels in HCC were identified by direct injection of radiopaque material into the tumor in 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 1 publication
1
22
0
Order By: Relevance
“…Numerous previous studies have demonstrated that the presence of either microscopic or macroscopic vascular invasion is the key risk factor for recurrence [18,19]. Intrahepatic metastasis via the portal venous system is generally accepted as an important mechanism for intrahepatic recurrence [20,21]. This study confirmed that vascular invasion in HCC patients with cirrhosis who underwent hepatectomy increased the chances of reducing long-term survival by 2.347 times.…”
Section: Discussionsupporting
confidence: 78%
“…Numerous previous studies have demonstrated that the presence of either microscopic or macroscopic vascular invasion is the key risk factor for recurrence [18,19]. Intrahepatic metastasis via the portal venous system is generally accepted as an important mechanism for intrahepatic recurrence [20,21]. This study confirmed that vascular invasion in HCC patients with cirrhosis who underwent hepatectomy increased the chances of reducing long-term survival by 2.347 times.…”
Section: Discussionsupporting
confidence: 78%
“…The presence of vascular invasion is considered to be the direct evidence of intrahepatic metastasis. Toyosaka et al proved that the HCC spread progressed from capsular invasion to extracapsular invasion, then to vascular invasion, and finally to intrahepatic metastasis (Toyosaka et al, 1996). This findings strongly suggests that IM is mainly attributable to early recurrence for HCC patients after curative resection.…”
Section: Discussionmentioning
confidence: 99%
“…Intrahepatic metastases via the portal venous system are widely accepted as a main mechanism for intrahepatic recurrence (Toyosaka et al, 1996). Hasegawa et al (2005) demonstrated that anatomic resection can help to reduce the possibility of early recurrence resulting from vascular invasion and had a better outcome than nonanatomic resection.…”
Section: Discussionmentioning
confidence: 99%